Collapsed photonic crystal fibre thermoluminescence dosimetry for external beam radiotherapy. Issue 1 (March 2023) - Begum, Mahfuza; Almohammed, Huda I.; Rahman, A.K.M. Mizanur; Abdul-Rashid, H.A.; Yusoff, Z.; Hamd, Zuhal Y.; Khandaker, Mayeen Uddin; Bradley, D.A.
Abstract: In measuring exposure to ionizing radiation various detectors and techniques have been developed. Current investigation is of key TL dosimetric responses of Ge-doped collapsed photonic crystal fibre (PCF), a form offering the advantage of greater sensitivity compared to more conventional single-mode optical fibers. The PCF samples that have been studied herein have been used to obtain external photon beam percentage depth doses (PDD), elevated sensitivity being desirable in providing a basis for the capture of the range of doses. Using a linac operated at 6 and 10 MV, the results show a favourable comparison with ionization chamber values (typically to within 5%). Threshold dose, reproducibility, and dose-rate dependency have also been characterized.